Optimisation and costing of faecal sludge management options for Lusaka's informal settlements. Issue 1 (6th October 2015) - Kennedy-Walker, Ruth; Holderness, Tomas; Alderson, David; Amezaga, Jaime M.; Paterson, Charlotte A.
Abstract : This paper presents a methodology to support the implementation of Faecal Sludge Management services in informal settlements in Lusaka, The Republic of Zambia. Abstract : Faecal Sludge Management (FSM) is achieving traction in developing countries as a technical solution for the safe management (collection, transportation and in some cases treatment and end-use/safe disposal) of Faecal Sludge (FS) captured by onsite systems. Whilst some approaches do exist the overall availability of tools, data and practical examples to support decision makers in the implementation of FSM services on the ground is limited. This study aims to address some of these sector limitations by presenting a long-term costing methodology that was developed for two informal settlements in Lusaka, The Republic of Zambia. The approach compares the costs associated with a number of feasible fixed infrastructure and transportation technology scenarios over a 25 year design period. Within the analysis a spatio-topological tool was utilised to model proposed FSM networks and allowed the path of least-time transportation to be identified. This was then used to calculate Net Present Value and Average Incremental Cost, for seven different FSM scenarios, over a 25 year design life. The results of the study show that FSM could provide an affordable solution for the provision of sanitation services to Lusaka's poorest communities. The research conducted aims to support planners in Lusaka but also presents a number of methodologies that could be beneficial to the wider sanitation sector.